Dipyridamole: A Drug with Unrecognized Antioxidant Activity - Ciacciarelli, Marco; Zerbinati, Chiara; Violi, Francesco; Iuliano, Luigi (Current Topics in Medicinal Chemistry, 2015)
Dipyridamole was introduced on the market as coronary vasodilator drug more than half a century ago and is still used as antithrombotic and vasodilator. Among cellular targets, it inhibits phosphodiesterases and raises extracellular levels of adenosine through inhibition of adenosine reuptake by red blood cells. As a consequence, endocellular levels of cyclic nucleotides are upregulated. The rise of cGMP in vascular smooth mu scle cells and of cAMP in platelets provide the mechanism of vasodilation and antithrombosis, which are further potentiated by the release of PGI2 consequent on the increase in endothelial cell cAMP. These effects support the use of dipyridamole in cardiovascular diseases in which the drug is approved for the secondary prevention of cerebrovascular events. On the other hand, dipyridamole has been shown to possess a potent, little perceived, antioxidant activity of potential use in the several fields where pathophysiological pathways are dependent on oxidative stress, including those occurring in atherosclerosis, thrombosis, CNS-related diseases, and cancer.
Keywords: Cancer